ANALYSIS OF MURABAHAH CONTRACTS IN CONSUMPTIVE FINANCING: A CRITICAL REVIEW OF THE EFFICIENCY AND POTENTIAL OF COVERT RIBA - SHARIA PERSPECTIVES, REGULATIONS, AND ACCOUNTING STANDARDS - Siti Umi Nurbaidah; Nur Hidayah; Muhajirin (RADJA PUBLIKA, 2025)
This study examines the practice of Murābaḥah contracts in consumptive financing in Islamic banks by highlighting their conformity to maqāṣid al-sharī'ah. Despite being the dominant instrument, the implementation of Murābaḥah is often criticized for resembling interest-bearing credit due to the absence of real ownership and risk of goods by banks. This research uses a qualitative-normative approach through the analysis of financial statements, DSN-MUI fatwas, OJK regulations, PSAK 102, as well as interviews with the Sharia Supervisory Board and sharia auditors. The framework of analysis is based on Ibn 'Āsyūr's perspective on the protection of property (ḥifẓ al-māl) and justice ('adl). The results of the study show the gap between fiqh norms, regulations, and accounting practices. Margins are recorded linearly resembling interest, ownership of goods is not disclosed, and financial statements fail to display the substance of the risk. As a contribution, this study proposes a model of margin determination based on 'iwāḍ (legitimate compensation for risk and effort) and recommends a reformulation of financial statements that is in line with maqāṣid. Calculation simulations confirm the risk of